The Retention of Learning Achievement in Natural Science with PDC Instructional Model (Preparing, Doing, Concluding) in Grade 8-th at Junior High School 02 of Umbulsari - Reni Nurhapsari (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2017)
This Research and Development study aimed to determine the retention of natural science learning achievement with the PDC Model (Preparing, Doing, Concluding). The subject of this research was the 8th students at The Public Junior High School 2 of Umbulsari during the even semester of 2015/2016 academic year. Data analysis applied qualitative descriptive. Retention of learning outcomes of Natural Science with PDC instructional model (Preparing, Doing, Concluding) was obtained from the scores of learning achievement after the implementation the PDC instructional model. The results of the average score of student retention were 97.61% high category in cycle 1, 98.23% high category in cycle 2, and 99.91% high category in cycle 3. All in all, it can be concluded the retention of Natural Science learning achievement with instructional model PDC (Preparing, Doing, Concluding) is classified as the high category.